Liver Injury in Children with COVID-19: A Systematic Review - Satrio Wibowo; Tita Luthfia Sari; Muhammad Irawan (The Indonesian Society of Pediatric Gastroenterology, Hepatology, and Nutrition, 2023)
Background: The rapid global spread of coronavirus disease 2019 (COVID-19) infection has become a major health issue with high morbidity and mortality rates. COVID-19 in children showed different unique presentations. Besides respiratory symptoms, a growing body of evidence indicates multi-organ manifestation, including liver involvement. In this regard, several data supported an association between COVID-19 infection and liver injury in adults, while on the other hand, there is compelling but currently limited evidence in children. In this systematic review, we summarize data of updated literature regarding the evidence of acute liver injury in children with COVID-19. Methods: Online scientific articles were explored on PubMed and Google Scholar databases using keywords. The systematic review was performed under the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines Results: The literature search yielded 238 articles, of which 16 were identified as relevant to the topic and met the inclusion criteria. A total of 564 pediatric patients were confirmed positive for COVID-19 by PCR examination, involving 298 (52.9%) boys and 266 (47.1%) girls with an age range of 1 day - 17 years. Liver injuries have been reported in pediatric COVID-19 patients, with prevalence ranging from 1.5 to 52%. Conclusion: SARS-CoV-2 virus infection in children shows a unique presentation. Several reports suggest that liver injury correlates with the severity of COVID-19 disease. Therefore, monitoring liver function in COVID-19 patients is important to assess the prognosis.